2017
DOI: 10.1161/circimaging.117.005447
|View full text |Cite
|
Sign up to set email alerts
|

Multiorgan, Multimodality Imaging in Cardiometabolic Disease

Abstract: Cardiometabolic disease, spanning conditions such as obesity to type 2 diabetes mellitus with excess cardiovascular risk, represents a major public health burden. Advances in preclinical translational science point to potential targets across multiple organ systems for early intervention to improve cardiometabolic health. Validation in clinical trials and translation to care would benefit from in vivo diagnostic techniques that facilitate therapeutic advancements. This review provides a state-of-the-art, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…2c and Extended Data Figs. [1][2][3]. For instance, in RNA-seq data comparing the atherosclerotic aortic arterial wall (AOR) of individuals with CAD with the healthy aortic wall of controls, coding genes were equally upregulated and downregulated (n = 1,727 and 1,652, respectively), whereas noncoding genes were predominantly upregulated (n = 9,047 and 560).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c and Extended Data Figs. [1][2][3]. For instance, in RNA-seq data comparing the atherosclerotic aortic arterial wall (AOR) of individuals with CAD with the healthy aortic wall of controls, coding genes were equally upregulated and downregulated (n = 1,727 and 1,652, respectively), whereas noncoding genes were predominantly upregulated (n = 9,047 and 560).…”
Section: Resultsmentioning
confidence: 99%
“…12 ) (the 'GRN' definition used in the current study). This broader correlation-based definition of GRNs has become widely accepted, because (1) it helps to answer concrete biological questions, and (2) it addresses limitations that are inherent in the traditional definition of gene-regulatory networks. A fundamental question in complex disease genetics is how genetic variation affects disease traits.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that NAFLD is more common in patients with IHD and combines many common risk factors, such as DM and obesity [ 2 , 5 , 6 , 11 ]. In this study, we defined MAFLD using the definition proposed by Eslam et al [ 12 ] and showed that 48.9% of patients had MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The association between MAFLD and physical dysfunction in patients with IHD can be attributed to several underlying mechanisms. Patients with NAFLD are often reported to develop sarcopenia; this can be attributed to the presence of insulin resistance, excess adipose tissue, and chronic low-grade inflammation in this population [ 1 , 6 , 36 ]. Hepatic steatosis and the resulting NAFLD can lead to additional chronic inflammation by secretion of inflammatory cytokines such as IL6, TNF-alpha, and leptin [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation